2022
DOI: 10.20961/plexus.v1i4.46
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekstrak Etanolik Daun Kelor (Moringa oleifera, Lam) Terhadap Nilai Ekspresi TNF-α Testis Tikus Wistar (Rattus norvegicus) Model Sindrom Metabolik

Abstract: Latar Belakang: Peningkatan angka penderita sindrom metabolik secara global dianggap mengkhawatirkan karena mengakibatkan komplikasi masalah kesehatan pada berbagai organ termasuk organ reproduksi pria. Infertilitas pada pria yang disebabkan oleh inflamasi kronik dan kematian sel yang terjadi pada sindrom metabolik erat kaitannya dengan peran TNF-α sebagai mediator inflamasi. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak etanolik daun kelor terhadap ekspresi TNF-α pada jaringan testis ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Research on the health benefits of Moringa has been widely reported. A study by Putri (2017) demonstrated that Moringa seed extract can significantly reduce ICAM-1 expression in the carotid tissue of Wistar rats. The primary objective of this study is to examine the impact of Moringa oleifera Lamk leaf extract on the expression of ICAM-1 in the aortic tissue of Wistar rats (Rattus norvegicus) with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the health benefits of Moringa has been widely reported. A study by Putri (2017) demonstrated that Moringa seed extract can significantly reduce ICAM-1 expression in the carotid tissue of Wistar rats. The primary objective of this study is to examine the impact of Moringa oleifera Lamk leaf extract on the expression of ICAM-1 in the aortic tissue of Wistar rats (Rattus norvegicus) with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that it is beneficial in improving the histological appearance of the testicle of Wistar rats with diabetes mellitus by reducing fat degeneration and necrosis 11 . The administration of Moringa oleifera leaves ethanolic extract can also decrease the expression value of TNF-α in metabolic syndrome models 12 . Therefore, this study aims to determine the effect of Moringa oleifera leaves on the histopathological appearance of the testes of Wistar rats induced with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%